Molecular Resources from Transcriptomes in the Brassicaceae Family - Lopez, Lua; Wolf, Eva M.; Pires, J. Chris; Edger, Patrick P.; Koch, Marcus A. (Frontiers in Plant Science, 2017)
The rapidly falling costs and the increasing availability of large DNA sequence data sets facilitate the fast and affordable mining of large molecular markers data sets for comprehensive evolutionary studies. The Brassicaceae (mustards) are an important species-rich family in the plant kingdom with taxa distributed worldwide and a complex evolutionary history. We performed SSRs (single short repeats) mining using de novo assembled transcriptomes from 19 species across the Brassicaceae in order to study SSR evolution and provide comprehensive sets of molecular markers for genetic studies within the family. Moreover, we selected the genus Cochlearia to test the transferability and polymorphism of these markers among species. Additionally, we annotated Cochlearia pyrenaica transcriptome in order to identify the position of each of the mined SSRs. While we introduce a new set of tools that will further enable evolutionary studies across the Brassicaceae, we also discuss some broader aspects of SSR evolution. Overall, we developed 2012 ready-to-use SSR markers with their respective primers in 19 Brassicaceae species and a high quality annotated transcriptome for Cochlearia pyrenaica. As indicated by our transferability test with the genus Cochlearia these SSRs are transferable to species within the genus increasing exponentially the number of targeted species. Also, our polymorphism results showed substantial levels of variability for these markers. Finally, despite its complex evolutionary history, SSR evolution across the Brassicaceae family are highly conserved and we found no deviation from patterns reported in other Angiosperms.